The effects of canning on B-vitamin retention in a model cat diet with an emphasis on thiamine - Trible, Shelby DeNoya (Kansas State University, 2016)
Water soluble B-vitamins play an integral role in normal metabolic function in cats. For example, thiamine deficiency results in anorexia, neurological impairment, and, in severe cases, death in a few weeks’ time. However, little research has addressed how these vitamins are affected during cat food canning. Thiamine is the most susceptible to degradation during this process, with less known about how it affects the other B-vitamins. Therefore, our objectives were to determine the effects of modifying processing parameters on thiamine and other water-soluble B-vitamins in a model canned cat food. In a series of five experiments, various processing parameters were adjusted: including cook (retort) time, batter moisture and temperature, pH, protein source, and the addition of sulfites. Pressure (172368.93 Pa) and temperature (121 ̊C) within the retort remained the same for all treatments. As retort time increased, thiamine concentration decreased (P ≤ 0.05). No loss of B-vitamin concentration was noted for thiamine, riboflavin, cobalamin, and pantothenic acid as batter moisture increased. Likewise, as batter temperature increased, concentration of riboflavin, niacin, pyridoxine, folic acid, and pantothenic acid remained constant (P ˃ 0.10). When different types of thiamine were included for supplementation, thiamine mononitrate tended to have a greater retention of the vitamin than thiamine hydrochloride (P = 0.12). The protein sources selected for the experiment included chicken as a control, beef liver, chicken liver, pork liver, salmon, tuna, and whitefish. The salmon, tuna, and whitefish were grouped together for analysis. Beef liver, chicken liver, and pork liver were grouped together for analysis. The vitamin retention of each group was compared. When compared to chicken or liver, thiamine retention was greatest in diets containing fish (P≤ 0.05). In addition, riboflavin, niacin, and cobalamin retentions were greatest (P≤ 0.05) in diets containing liver. The addition of sulfites came from dehydrated potatoes added to thediets in exchange for rice. Thiamine tended to decrease in those diets with sulfite containing dehydrated potatoes (P= 0.07) compared to diets containing rice. Pyridoxine and pantothenic acid retention decreased in diets containing dehydrated potatoes (P≤ 0.05) compared to diets containing rice. The largest negative impact on thiamine retention was time in the retort; cobalamin, folic acid, and riboflavin were also negatively affected. Including sulfite-containing potatoes in the diet tended to decrease thiamine, pyridoxine, and pantothenic acid. It was expected that diets containing chicken would retain more thiamine than those formulated with fish and liver. However, diets containing fish retained more thiamine, pyridoxine, and pantothenic acid. Therefore, it appears that processing and diet composition can affect the B-vitamin content of canned cat foods and must be accounted for when producing commercial products.
Keywords: B-Vitamins; Pet Food; Thermal ProcessingThiamine; Agriculture, General (0473); Animal Sciences (0475)